Elementary school teacher candidates’ opinions on the social studies program regarding its suitability to train problem solving and decision making abilities - (:unkn) unknown (My University, 2011)
Bu araştırmanın amacı, İlköğretim Sınıf Öğretmenliği Programı öğretmen adaylarının Sosyal Bilgiler Öğretim Programı’nın problem çözme ve karar verme becerilerini kazandırmadaki etkililiğine ilişkin görüşlerini belirlemektir. Araştırmanın örneklemini Marmara Üniversitesi Atatürk Eğitim Fakültesi Sınıf Öğretmenliği Anabilim Dalı’nda öğrenim gören 128 öğrenci oluşturmaktadır. Araştırma tarama modeli kullanılarak gerçekleştirilmiştir. Araştırmada veri toplama aracı olarak üçlü likert tipi bir ölçek geliştirilerek geçerlik ve güvenirlik analizleri yapılmıştır. Elde edilen veriler aritmetik ortalama, standart sapma, t-testi ve varyans analizi teknikleri kullanılarak çözümlenmiştir. Bulgulara göre sınıf öğretmeni adayları İlköğretim Sosyal Bilgiler Öğretim Programı’nı problem çözme ve karar verme becerilerini kazandırmada etkili bulmuşlardır.

This research aims at outlining the opinions of elementary school teacher candidates on the Primary School Social Studies Teaching Program in relation to Program’s suitability to train problem solving and decision making abilities. Problem solving and decision making are parallel abilities since they both have common specifics. In order to realize the Program in practice, it is important for teacher candidates to recognize their abilities on problem solving and decision making. In this research, survey method has been used. Examples are composed of 128 students studying in Marmara University Atatürk Faculty of Education, Elementary Education Department. In this research triple likert type scale which is valid and reliable is used. Data obtained from this research is analysed through arithmetic average, standard dialect, t-test and varyans analysis. According to the results of the survey, teacher candidates consider the Program effective for training problem solving and decision making abilities.
Sınıf öğretmenliği programı öğretmen adaylarının sosyal bilgiler programının problem çözme ve karar verme becerilerini kazandırmadaki etkililiğine yönelik görüşleri
Keywords: Eğitim, Eğitim Araştırmaları